Genome-wide miRNA profiling in myelodysplastic syndrome with del(5q) treated with lenalidomide - Merkerova, Michaela Dostalova; Krejcik, Zdenek; Belickova, Monika; Hrustincova, Andrea; Klema, Jiri; Stara, Eliška; Zemanova, Zuzana; Michalova, Kyra; Cermak, Jaroslav; Jonasova, Anna (European journal of haematology, 2015)
OBJECTIVES: Lenalidomide is a potent drug with pleiotropic effects in patients with myelodysplastic syndrome (MDS) with deletion of the long arm of chromosome 5 [del(5q)]. We investigated its effect on regulation of microRNA (miRNA) expression profiles in del(5q) patients with MDS in vivo. METHODS: We used miRNA expression microarrays to study changes in miRNA levels in peripheral blood CD14+ monocytes collected from patients before and during lenalidomide treatment and compared them with those from healthy donors. RESULTS: Before treatment, we observed strong upregulation of pro-apoptotic miR-34a and miR-34a* that diminished during lenalidomide exposure. Upregulation of HOX-related miR-196b and erythroid-specific miR-451 seen in untreated patients remained unchanged after the treatment. At the time of hematologic response, expression of several miRNAs clustering to the 14q32 locus was reduced. Additionally, we focused more deeply on miRNAs from the 5q commonly deleted region and found that levels of miR-378 and miR-378* followed haploinsufficiency trend. CONCLUSIONS: This report describes changes in miRNA expression in del(5q) patients with MDS treated with lenalidomide, likely arising from deregulation of pathways implicated in lenalidomide action.
Keywords: chromozomální delece; regulace genové exprese u nádorů; Genetic Loci; primární buněčná kultura; Female; thalidomid; sestřih RNA; Genome-Wide Association Study; Thalidomide; del(5q); RNA Splicing; myelodysplastic syndromes; Haploinsufficiency; ženské pohlaví; Chromosomes, Human, Pair 14; Gene Expression Regulation, Neoplastic; imunologické faktory; lenalidomid; Leukocytes, Mononuclear; lidé; Lenalidomide; signální transdukce; studie případů a kontrol; lidské chromozomy, pár 14; haploinsuficience; stanovení celkové genové exprese; Signal Transduction; Myelodysplastic Syndromes; myelodysplastické syndromy; Immunologic Factors; Male; lidské chromozomy, pár 5; Case-Control Studies; Aged; Chromosome Deletion; mikro RNA; celogenomová asociační studie; miRNA; Chromosomes, Human, Pair 5; Primary Cell Culture; MicroRNAs; lidé středního věku; senioři; mužské pohlaví; Anemia, Macrocytic; genetické lokusy; Middle Aged; lenalidomide; Gene Expression Profiling; leukocyty mononukleární; makrocytární anemie; Humans